ChemInform Abstract: Enantioselectivity Switch in Copper‐Catalyzed Conjugate Addition Reactions under the Influence of a Chiral N‐Heterocyclic Carbene—Silver Complex. Issue 24 (27th May 2016) - Matsumoto, Keitaro; Nakano, Yuki; Shibata, Naoatsu; Sakaguchi, Satoshi
Abstract: The asymmetric 1, 4‐addition of diethylzinc to 2‐cycloalken‐1‐ones in presence of a copper catalyst with a chiral ligand affords 3‐ethylcycloalkanones.